Analysis of the Effect of Remuneration, Workload, and Organizational Commitment on Organizational Effectiveness among Account Representative Employees at Primary Tax Offices (KPP Pratama) in East Jakarta - La Ode Mohammad Thomas Khan (Privietlab, 2024)
This study aims to analyze the effect of remuneration, workload, and organizational commitment on organizational effectiveness at the Primary Tax Offices (KPP Pratama) in East Jakarta. The research employs a quantitative approach using a survey method, where data were collected through questionnaires distributed to employees. The data were analyzed using multiple linear regression to examine both partial and simultaneous effects of the independent variables on organizational effectiveness. The results indicate that remuneration has a positive and significant effect on organizational effectiveness, suggesting that better compensation systems can enhance employee performance and contribute to organizational goals. Workload also shows a positive and significant effect, indicating that an appropriate distribution of work can improve employee productivity and efficiency. Furthermore, organizational commitment has a strong positive and significant influence, reflecting that employees with higher commitment tend to contribute more effectively to the organization. Simultaneously, remuneration, workload, and organizational commitment significantly affect organizational effectiveness. These findings highlight that the combination of fair compensation, balanced workload, and strong employee commitment plays a crucial role in achieving optimal organizational performance. Therefore, organizations are encouraged to improve these aspects to enhance overall effectiveness.